Associations between health‐related family environment and objective child sleep quality. (11th February 2021) - Williams, Bethany D; Whipps, Jonathon; Sisson, Susan B; Guseman, Emily H
Abstract : Aim: This study aimed to assess the relationship between the family environment and behaviours with objective child sleep quality. Methods: Twenty‐four children (aged 2–5 years) and their parents participated. Child sleep was assessed by accelerometer. Health of the family environment was quantified using the Family Nutrition and Physical Activity Screening Tool (FNPA). Exact Wilcoxon rank sum tests and linear regression were used to determine associations between FNPA scores and child sleep. Results: Healthier Total FNPA, Physical Activity FNPA, and Sleep Routine scores were associated with earlier bedtime. Healthier Sleep Routine score was associated with more total minutes of sleep per night. Healthier screen time‐related FNPA construct scores were associated with earlier bedtime. Conclusions: A composite score of family environment and behaviours, including physical activity‐ and nutrition‐related constructs, was related to child sleep quality. Focus should be placed on the obesogenic family environment and healthy sleep routines to promote overall health among pre‐school‐aged populations.